Reconstruction of B-0->J/psi K-S(0) and measurement of ratios of branching ratios involving B->J/psi K* and B+->J/psi K+ - Abe, F; Albrow, MG; Amendolia, SR; Amidei, D; Antos, J; AnwayWiese, C; Apollinari, G; Areti, H; Atac, M; Auchincloss, P; Azfar, F; Azzi, P; et al. (1996)
We report on the reconstruction of the decay mode B0 → J/ψKS 0 using 19.3 pb-1 of data collected by the Collider Detector at Fermilab in p̄p collisions at s√ = 1.8 TeV. A signal of 41.8 ± 6.9 events, with a signal-to-background ratio of 9:1, is observed. Three additional decay modes B+ → J/ψ K +, B0 → J/ψK* (892)0 and B+ → J/ψ K* (892)+ are reconstructed. We measure three ratios of branching ratios, each one relative to the B+ → J/ψ K+ mode. We also report the ratio of decay rates, Γ(B → J/ψ K*)/Γ(B → J/ψ K), for the vector-vector relative to the vector-pseudoscalar modes, to be 1.32 ± 0.23(stat) ± 0.16(syst).